Survey of the communities of Pampanga as a basis for the evaluation of subject matter content in general science - Sangalang, Luz E. 1922- (1956)
The author attempted to analyze community life in Pampanga with special emphasis on aspects having direct implications on general science education.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Science